'Building back better' in the context of multi‐hazards in the Caribbean. (25th May 2022) - Jones, Eleanor; Doughorty, Kristinia; Brown, Pietra
Abstract : The multi‐hazard vulnerability of Small Island Developing States in the Caribbean has underpinned the repeated saga of destructive natural and anthropogenic events that have disrupted land, livelihoods, the economy, and society over the past several decades. Preparedness and response have been the focus of national governments and regional entities and the repeated battering calls into question the concept of recovery and 'building back better'. This paper examines the concept of recovery and 'building back better' in the context of the Caribbean, paying particular attention to the experience of the selected countries of Antigua and Barbuda, the Bahamas, Dominica, Guyana, Jamaica, and Saint Vincent and the Grenadines. These nations have recently been impacted by different disasters, ranging from storms to earthquakes to volcanic eruptions. This paper also explores the similarities among the recommendations concerning recovery needs, presenting key insights into suggested approaches for an inclusive people‐centred recovery process that 'builds back better'.